NGC 2309: A Relatively Young Open Cluster Projected onto a Random Stellar Concentration - Piatti, Andres Eduardo (2010)
We have obtained CCD photometry down to for the open cluster NGC 2309 and its surrounding field. Twenty three probable cluster members have been identified for the first time on the basis of sound photometric criteria. Because NGC 2309 is a relatively poor cluster projected onto a rich star field showing density fluctuations, the frequently used membership criteria based on stellar density profiles or proper motion measurements would not be enough to assess the star membership status if employed independently. We estimated a cluster radius of 7.9´ and a radius at half the maximum of the cluster density profile of 1.7´. Based on the best fits of isochrones computed by the Geneva group to the cluster color-magnitude and color-color diagrams, previously shifted by the cluster reddening (E(B-V)=0.32) and distance (d=2.5 kpc), we derived the cluster age (250 Myr) and metallicity ([Fe/H]=0.0). If an 8.5 kpc distance from the Sun to the center of the Galaxy is assumed, then NGC 2309 is found to be located just in front of the Perseus spiral arm.